Model Pembelajaran POE (Predict Observe Explain) Meningkatkan Hasil Belajar Siswa - dina puspitasari dina; Tri Ariani (CV. ITTC INDONESIA, 2024)
ABSTRACT The research method used is a literature review. A literature review requires systematic stages, to carry out the identification, evaluation and synthesis stages of research works and studies that have been completed by previous researchers. This research was carried out by searching for articles that were similar to the research title via Google Scholar by getting 8 articles that had been selected and getting 4 articles and published or published 85 articles. After being selected, they got 3 articles with a period of 2017-2022 which had indexed sinta 2 and 3 , which uses Indonesian. Collecting articles in Indonesian language that meet the requirements that have been determined according to needs, such as title, variables and year of publication of the journal are required within the 20172024 time frame. The benefits of creating a POE Learning Model are to improve student learning outcomes later. Based on the background of this research, it can be formulated, namely how to improve student learning outcomes through the POE (Predict, Observe, Explain) learning model in science learning and the aim of this research is to improve science learning outcomes through the POE (Predict, Observe, Explain) learning model. ) in science learning and can be an alternative learning model in improving learning outcomes. Keywords: Application of Learning Models, Poe (Predict, Observe, Explain), Improving Learning Outcomes, Mts Students